2002
DOI: 10.1074/jbc.m208016200
|View full text |Cite
|
Sign up to set email alerts
|

DNA Interstrand Cross-links of the Novel Antitumor Trinuclear Platinum Complex BBR3464

Abstract: It is now well established that polynuclear platinum compounds in which two or three platinum coordination units are linked in a linear fashion compose an important new class of anticancer drugs [1,2]. The first clinical compound, currently denoted BBR3464 (see Fig. 1A), is a bifunctional trinuclear DNA-binding agent with an overall 4ϩ charge (3). The phase I trials (4, 5) demonstrated a clear pattern of responses in cancers not normally treatable with cisplatin (cis-diamminedichloroplatinum(II)) (see Fig. 1A)… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
139
1
2

Year Published

2003
2003
2011
2011

Publication Types

Select...
8
1

Relationship

6
3

Authors

Journals

citations
Cited by 148 publications
(145 citation statements)
references
References 68 publications
3
139
1
2
Order By: Relevance
“…The DNA bending toward the minor groove and unwinding due to one 1,3-intrastrand adduct of trans-(PtCl 2 (NH 3 )(pip)) has been found 30 Ϯ 2 and 8 Ϯ 2°, respectively (the direction of the bend was determined using the duplex (TGTGTϩ(A/T) 5 )(32) (Fig. 1B) in the same way as in our recent papers (21,32,33)). Moreover, the ligation of the 21-and 22-bp duplexes containing 1,3-intrastrand CL of trans-(PtCl 2 (NH 3 )(pip)) resulted in the formation of circles, suggesting that the 1,3-intrastrand CLs of this transplatin analogue increased the flexibility of the double helix (29,34).…”
Section: Cellular Platinummentioning
confidence: 78%
See 1 more Smart Citation
“…The DNA bending toward the minor groove and unwinding due to one 1,3-intrastrand adduct of trans-(PtCl 2 (NH 3 )(pip)) has been found 30 Ϯ 2 and 8 Ϯ 2°, respectively (the direction of the bend was determined using the duplex (TGTGTϩ(A/T) 5 )(32) (Fig. 1B) in the same way as in our recent papers (21,32,33)). Moreover, the ligation of the 21-and 22-bp duplexes containing 1,3-intrastrand CL of trans-(PtCl 2 (NH 3 )(pip)) resulted in the formation of circles, suggesting that the 1,3-intrastrand CLs of this transplatin analogue increased the flexibility of the double helix (29,34).…”
Section: Cellular Platinummentioning
confidence: 78%
“…1B that contained two guanine (G) residues in the top strand) were prepared as described (9,19,20). The interstrand cross-linked duplexes were also prepared and characterized in the same way as described previously (21,22).…”
Section: Methodsmentioning
confidence: 99%
“…Some strategies have been applied for the design of new drugs, such as the use of other types of ligands, in order to reduce side effects and increase the antitumoral effect of the drug. Much attention has also been focused on synthesis of new dinuclear or trinuclear species, like the compound [trans-PtCl(NH 3 ) 2 ) 2 (l-trans-Pt-(NH 3 ) 2 (NH 2 (CH 2 ) 6 -NH 2 ) 2 )](NO 3 ) 4 (BBR3464) which is in Phase II clinical trial and showed consistent activity against cisplatin-resistant human tumors [6,7].…”
Section: Introductionmentioning
confidence: 99%
“…The presence of the linkers allows for innovative mechanisms of DNA interaction, such as "long-distance" inter-and intrastrand crosslinks within the DNA helix [5], which probably contribute to the improved antitumor efficacy exhibited by some of these complexes, namely a clear pattern of responses in cancers not normally treatable with cisplatin [6,7]. In order to overcome cisplatin limitations, several other routes have been pursued, such as the synthesis of drugs based on palladium.…”
Section: Introductionmentioning
confidence: 99%